Enhancing food security in Latin America with forage legumes - Muir, James P; Tedeschi, Luis O; Dubeux, José C.B.; Peters, Michael; Burkart, Stefan (Asociacion Latinoamericana de Produccion Animal, 2017)
Forage legumes could enhance ruminant production in Latin America far more than they currently do. With a few instructive exceptions, decades invested in domesticating, testing and divulgating pasture and rangeland leguminous species, have had limited impact. Reasons for this include lack of end-user involvement in research and development, inadequate commercial seed sources, low persistence under grazing, and substitution with industrial nitrogen fertilizer. Current efforts to improve legume adoption include research on domestication of new species especially natives, grass-legume mixtures, silvopasture, protein banks, and mitigating anti-nutritive components. Future challenges might include a greater focus on economical seed production, establishment in multi-species plantings, persistence under grazing, sustainable intensification, domesticating local germplasm, ecosystems services, multiple uses, harnessing condensed tannins, and greater crop-livestock integration of legumes. We believe that these and other innovations make the future of forage legumes very promising in Latin America.